EDUKASI GIZI BAGI IBU BALITA DI WILAYAH KERJA PUSKESMAS LAPAI KECAMATAN NANGGALO KOTA PADANG - Azrimaidaliza Azrimaidaliza; Welly Femelia; Nadia Nur Chalida; Rahmi Putri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Nutritional problems in children under five age show an increasing trend in Indonesia, including Padang City. One of these nutritional problems is stunting. Stunting conditions can have an impact on the growth and development of children at a later age and even at the risk of developing degenerative diseases in adulthood. The purpose of nutrition education for mothers is to increase the knowledge and understanding of mothers about the importance of the First 1000 Days of Life in overcoming the nutritional problems among children. Activity was direct counseling to small groups about 1000 Days of Life and supported by leaflet. The target of the activity is pregnant women and mothers with toddlers who visit one of the Posyandu in Lapai Health Center Work Area, Nanggalo District, Padang City. Partner of this activity is Lapai Health Centre, mainly coorporate with nutritionist and health workers, including cadres in this health centre. Monitoring and evaluation of the success of activities are assessed from the results of the pre- and post-test submitted to the target of the activity. Educational activities were carried out well even though they were still in the pandemic and the implementation of social distancing. This activity was attended by 12 mothers of toddlers, 2 cadres, and 2 health workers from Lapai Health Center. Based on the results of the pre and post-test, it was found that there is an increase in the knowledge of mothers (66.7% to 83.3%). Thus, educational activities in the form of counseling through collaboration with educational institutions and health institutions can be carried out through Posyandu every month to prevent nutritional problems on children under five age.